Gender-Based Violence in South-East Asia Policy in Practice - Nurtjahyo, Lidwina Inge.; Wicaksono, Mochammad Arief (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents new research on gender-based violence in Southeast Asia, bringing together varied scholarly work in law, policy, and practice. It enables a greater understanding of violence against women as an international concern, highlighting particular issues that arise in the region. Against a background of international obligations to ensure women's rights through laws and policies that are geared at ending violence against women and girls, this research documents the state failures, individual shame and fear, and societal culture that collectively affects the reporting, investigation, prosecution of perpetrators, and protection of victims. The research explores differing legal mechanisms both internationally, and within nation states, relating to cases of physical and sexual violence. It recognizes the need for functioning mechanisms to ensure women can report their cases safely and be provided with protective and therapeutic services in a way that is systematic, effective, and measurable. Laws and court decisions are analyzed, crisis and safety centers are examined, and in-depth interviews are conducted with actors and NGOs with relevant roles and functions in the mechanism of cases of violence against women. The result is a comprehensive assessment of the incalculable harm it does within Southeast Asian society, and the obstacles it presents for law enforcement. The chapters uncover mechanisms with unique characteristics across Southeast Asia, providing a nuanced understanding of the cultural and social backgrounds, as well as the religious structures, that can both help and hinder suitable frameworks. It is relevant to scholars, policymakers, and practitioners in law, criminology, and gender sociology. "This is a valuable contribution towards empowering the women of South East Asia out of victimhood to valued equality, involvement in governance and leadership through the elimination of violence and discrimination and an excellent resource not just for those working in this field but for those involved in law making, the media and the people of South East Asia." - Professor Felicity Gerry QC, Barrister at Crockett Chambers Melbourne and Libertas Chambers, London, and Professor of Legal Practice at Deakin University and Honorary Professor at Salford University.
Foreword -- Chapter 1. Why the State Must Regulate? One Stop Crisis Center for Violence Against Women Cases: Some Notes from Southeast Asia -- Chapter 2. Research on Gender-based Violence: Some Notes on Comparative Study -- Chapter 3. Feminist Legal Analysis on The Rules of Handling Cases of Violence Against Women: Comparative Study on Timor Leste, Malaysia, Thailand, Singapore, and Indonesia -- Chapter 4. Defining Rape in Indonesia: A Never-ending Struggle -- Chapter 5. Sexual Violence on The Higher Education Institution -- Chapter 6. Indonesia and Peacekeeping Operations: Protection of Women's Rights in Africa under MINUSCA -- Chapter 7. The Silence Scream: Lesson from Violence Against Women Under Religion -- Chapter 8. The Role of Forensic Institution in Handling Violence Against Women in COVID-19 Pandemic: Forensic Perspective -- Chapter 9. Victim Protection of Multiple Victimization in Domestic Violence: A Right Way to Go? -- Chapter 10. How NGO Handle Domestic Violence Cases During COVID-19 Pandemic: Case Study in LBH APIK Jakarta -- Chapter 11. Recommendations on The Prevention of Female Genital Mutilation in Indonesia: Comparative Study Indonesia and Egypt -- Chapter 12. Multidisciplinary Research on Gender Based Violence: Collaboration in Knowledge and Practice.
Keywords: Sex; Law; Social policy; Criminology; Gender Studies; Law; Social Policy; Sexuality Studies; Asian Criminology